The Cluster Active Archive Studying the Earth's Space Plasma Environment - Laakso, Harri; Taylor, Matthew; Escoubet, C. Philippe; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
Since the year 2000 the ESA Cluster mission has been investigating the small-scale structures and processes of the Earth's plasma environment, such as those involved in the interaction between the solar wind and the magnetospheric plasma, in global magnetotail dynamics, in cross-tail currents, and in the formation and dynamics of the neutral line and of plasmoids. This book contains presentations made at the 15th Cluster workshop held in March 2008. It also presents several articles about the Cluster Active Archive and its datasets, a few overview papers on the Cluster mission, and articles reporting on scientific findings on the solar wind, the magnetosheath, the magnetopause and the magnetotail.
Products and Services of the Cluster Active Archive -- Cluster Active Archive: Overview -- ASPOC Data Products in the Cluster Active Archive -- Cluster Ion Spectrometry (CIS) Data in the Cluster Active Archive (CAA) -- Digital Wave Processor Products in the Cluster Active Archive -- EDI Data Products in the Cluster Active Archive -- The EFW Data in the CAA -- FGM Data Products in the CAA -- PEACE Data in the Cluster Active Archive -- RAPID Products at the Cluster Active Archive -- STAFF Instrument Products Distributed Through the Cluster Active Archive -- Cluster Wideband Data Products in the Cluster Active Archive -- The WHISPER Relaxation Sounder and the CLUSTER Active Archive -- ESOC Data Products in the CAA -- Tools for the CAA Data Analysis -- QSAS, QM Science Analysis Software -- Flexible Tools for Accessing the Cluster Archives -- AMDA, Automated Multi-Dataset Analysis: A Web-Based Service Provided by the CDPP -- Cluster CAA Module for PaPCo -- Measurement Techniques and Calibration Routines -- Electron Density Estimation in the Magnetotail: a Multi-Instrument Approach -- Cluster-PEACE In-flight Calibration Status -- Generation and Validation of Ion Energy Spectra Based on Cluster RAPID and CIS Measurements -- Magnetospheric Missions -- The Cluster Mission: Space Plasma in Three Dimensions -- Double Star: Mission, Instruments and Joint Observations -- Observations of Solar Wind and Magnetosheath -- Effect of Shock Normal Orientation Fluctuations on Field-Aligned Beam Distributions -- Wave Number Spectra in the Solar Wind, the Foreshock, and the Magnetosheath -- Cluster Hot Flow Anomaly Observations During Solar Cycle Minimum -- On the Growth of Mirror Mode Waves in the Magnetosheath Based on Cluster Observations -- Observations of Magnetopause and Cusp -- Mixed Azimuthal Scales of Flux Transfer Events -- Perspectives Gained from a Combination of Polar, Cluster and ISEE Energetic Particle Measurements in the Dayside Cusp -- Energetic Particles in the Cusp: A Cluster/RAPID View -- Observations of Magnetospheric Tail -- Plasma Flow Reversals in the Magnetotail and Their Implications on Substorm Models -- Spatial and Temporal Structures in the Vicinity of the Earth$1 (Bs Tail Magnetic Separatrix Cluster Observations -- Cluster Observations of Energy Conversion Regions in the Plasma Sheet -- Acceleration of >40 keV Electrons in Near-Earth Magnetotail Reconnection Events -- Evolution and Energization of Energetic Electrons in the Inner Magnetosphere -- Erratum.s
Keywords: Physics; Physical geography; Astrophysics; Physics; Extraterrestrial Physics, Space Sciences; Geophysics/Geodesy.